Effects of overnight military training and acute battle stress on the cognitive performance of soldiers in simulated urban combat - Passi, Tomi; Lukander, Kristian; Laarni, Jari; Närväinen, Johanna; Rissanen, Joona; Vaara, Jani P.; Pihlainen, Kai; Kallinen, Kari; Ojanen, Tommi; Mauno, Saija; Pakarinen, Satu (Frontiers in Psychology, 2022)
Understanding the effect of stress, fatigue, and sleep deprivation on the ability to maintain an alert and attentive state in an ecologically valid setting is of importance as lapsing attention can, in many safety-critical professions, have devastating consequences. Here we studied the effect of close-quarters battle (CQ battle) exercise combined with overnight military training with sleep deprivation on cognitive performance, namely sustained attention and response inhibition. In addition, the effect of the CQ battle and overnight training on cardiac activity (heart rate and RMSSD) during the cognitive testing and the relationship between cardiac activity and cognitive performance were examined. Cognitive performance was measured with the psychomotor vigilance task (PVT) and the sustained attention to response task (SART). Altogether 45 conscripts participated in the study. The conscripts were divided into control (CON) and experimental (EXP) groups. CON completed the training day after a night of sleep and EXP after the overnight military training with no sleep. Results showed that the effect of the overnight training on cognitive performance and the between-group difference in HR and HRV depended on the cognitive test. Surprisingly, the cognitive performance was not largely affected by the CQ battle. However, as expected, the CQ battle resulted in a significant decrease in RMSSD and an increase in HR measured during the cognitive testing. Similarly, the HR parameters were related to cognitive performance, but the relationship was found only with the PVT. In conclusion, fatigue due to the overnight training impaired the ability to maintain sufficient alertness level. However, this impairment in arousal upregulation was counteracted by the arousing nature of the SART. Hence, the conscripts´ cognitive performance was mainly preserved when performing a stimulating task, despite the fatigue from the preceding night´s sleep loss and physical activity.